Complications after resection of colorectal cancer in a public hospital and a private hospital. Issue 3 (23rd May 2014) - Bokey, Les; Chapuis, Pierre H.; Keshava, Anil; Rickard, Matthew J. F. X.; Stewart, Peter; Dent, Owen F.
Abstract Background To our knowledge, immediate post‐operative complication rates after resection of colorectal cancer (CRC) have not been compared between public and private hospitals in the Australian health care system. We compared the frequency of surgical and medical complications between a public tertiary referral hospital and a private hospital. Methods Data were drawn from a prospective registry of all patients having a resection for CRC between 2000 and 2010 performed by members of the Concord Hospital colorectal surgical unit, either at this hospital or at a single private hospital with which they were affiliated. Complication rates were compared after adjustment for preoperative and perioperative features by logistic regression. Results Among the 16 surgical complications, the only significant difference after adjustment for other features was a higher rate of septicaemia in the public hospital (odds ratio (OR) 2.2, 95% confidence interval (CI) 1.1–4.6). Among the seven medical complications, the only significant differences were a higher risk of cardiac complications in patients with cardiac co‐morbidity (OR 1.8, 95% CI 1.1–3.0) and of respiratory complications in patients without respiratory co‐morbidity (OR 3.1, 95% CI 2.2–5.9) in the public hospital. Conclusion In this study, where the same group of surgeons performed all reported CRC resections in the two hospitals, no independent effect of the type of hospital was found on 15 of 16 surgical complications and 5 of 7 medical complications. Type of hospital had no impact on rates of specific complications apart from septicaemia and cardiorespiratory complications, which were higher in the public hospital.